Investigation of schiff bases as corrosion inhibitors for mild steel in im sulfuric acid media / Indra Totoh - Totoh, Indra (Faculty of Applied Sciences, 2009)
Three Schiff base compounds, {[(lE)-(4-chlorophenyl)methylene]amino}phenol (Cben-ap), 2-[2-hydroxybenzylidene)amino]phenol (Sal-ap) and 2-{(E)-[(4- anilinophenyl)-imino]methyl}phenol (Sal-NPD) have been synthesized by the condensation of appropriate aldehydes and amines. Cben-ap is a light green crystal with 55 % yield, Sal-ap is an orange crystal with 78 % yield, Sal-NPD is a dark green crystal with 72 % yield. The structure of the Schiff bases are investigated using elemental analysis, IR spectroscopy, NMR spectroscopy and melting point determination. Results obtained from elemental analysis are closely matched the theoretical/literature values. These indicate that the intended products of Cben-ap, Sal-ap and Sal-NPD have been successfully obtained. The v(C=N) peaks are assigned at 1625, 1631 and 1619 cm"1, respectively. The inhibiting action of these Schiff bases toward the corrosion of mild steel in 1 M H2SO4 solution has been studied using the weight loss method, with inhibitor concentrations of 1 x 10"5 to 1 x 10"2 M for a 7 day exposure. It is found that the inhibition efficiency increases with increasing inhibitor concentration, with Cben-ap exhibited the highest corrosion inhibition property of 92.29% at 1 x 10"3 M, followed by Sal-ap which exhibited the second highest corrosion inhibition of 90.39% at 1 x 10"2 M and Sal-NPD around 82.00 % at 1 x 10"4 M.